Efeitos de compostos histaminérgicos no desempenho motor de camundongos submetidos ao modelo animal de neurotoxina 6-OHDA - Fernandes, Elayne Borges (Universidade Federal de São Carlos, 2023)
The modulation of the histaminergic system under the dopaminergic system has attracted particular attention, due to a potential neuroinflammatory effect of histamine. In Parkinson's Disease (PD), whose primary cause is still unknown, neuronal neuroinflammation may trigger dopaminergic neurotoxicity. A recent hypothesis is related to the activation of microglia mediated by the H4 histaminergic receptor. However, so far, there are no studies investigating the motor behavior against the modulation of the histaminergic system under the dopaminergic system in the animal model of the neurotoxin 6-hydroxydopamine (6-OHDA). Our aim was to investigate the effect of histaminergic compounds on motor performance in the animal model of the 6-OHDA neurotoxin. We used 120 naïve male mice (Swiss albino), which were submitted to neuronal damage induced by hemiestriatal injections of 6-OHDA and, after two weeks, received systemic injections of L.-histidine (Exp. 1), Thioperamide (Exp. 2 ) and VUF-8430 (Exp. 3) and were evaluated through behavioral tests, namely open field, rotarod and balance beam on two consecutive days. Statistical analysis was performed using two-way analysis of variance (ANOVA) for repeated measures, where we evaluated the performance of the animals. P values < 0.05 were considered statistically significant. For Exp.1, two-way ANOVA in the open field showed statistical differences in relation to groups and test days (p=0.001750); on the balance beam it indicated statistical differences on the test days (p=0.003838), and on the rotarod it indicated statistical differences between the test groups, (p=0.007008). For Exp. 2 ANOVA showed no statistically significant intragroup difference in the open field (p=0.242618) and rotaroad (p=0.408666); between groups in open field (p=0.432498) and rotaroad (p= 0.119649); and in the interaction between days and groups in the open field (p=0.214738), and in the rotaroad (p= 0.987078). While on the balance beam presented difference only within the group (p=0.004725), and between groups (p=0.303353) and in the interaction between days and groups (p=0.064281), there was no significant difference. And for Exp. 3 ANOVA in the open field indicated that there was a difference between days (p=0.000131) and between groups (p=0.004990); on the balance beam, there were no significant intragroup differences (p=0.694178); between groups (p=0.083342) and in the interaction between days and groups (p=0.075682); and in the rotarod it indicated that there was a difference between the days of the groups (p=0.013951). We found that LH had a positive influence on the motor performance of mice subjected to hemistriatal injury with 6-OHDA, and that the H4 receptor agonist was able to inhibit locomotor activity and worsen the balance of mice with neurotoxic injury
Effects of histaminergic compounds on the motor performance of mice submitted to the animal model of the neurotoxin 6-OHDA
Keywords: Sistema histaminérgico; Sistema dopaminérgico; 6-OHDA; Modelo animal; Comportamento motor; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL